2015
DOI: 10.1016/j.jnucmat.2014.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pores and He bubbles on the thermal transport properties of UO2 by molecular dynamics simulation

Abstract: The thermal conductivities of UO 2 single crystals containing nanoscale size pores and He gas bubbles are calculated using non-equilibrium molecular dynamics as a function of pore size and gas density in the bubble. As expected, the thermal conductivity decreases as pore size increases, while the decrease in thermal conductivity is determined to be more substantial than the predictions of traditional analytical models by Loeb and Maxwell-Eucken. However, the recent model of Alvarez, which is applicable when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 62 publications
3
31
0
Order By: Relevance
“…Specifically relating to 259 fission gas distribution, it is possible that any secondary phases of U 5 Si 4 /USi that precipitate due 260 to burnup induced variations in stoichiometry, may act as multiple nucleation sites for fission gas 261 bubbles. If these precipitates reside as intra-granular inclusions, their formation may contribute 262 to the highly dense fission gas bubble microstructure observed experimentally [34] [38]. 263…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically relating to 259 fission gas distribution, it is possible that any secondary phases of U 5 Si 4 /USi that precipitate due 260 to burnup induced variations in stoichiometry, may act as multiple nucleation sites for fission gas 261 bubbles. If these precipitates reside as intra-granular inclusions, their formation may contribute 262 to the highly dense fission gas bubble microstructure observed experimentally [34] [38]. 263…”
Section: Discussionmentioning
confidence: 99%
“…The phase diagram of Domagala is reproduced in Figure 1 (the β→γ U 3 Si 36 phase transition at 1048 K as reported by Remschnig et al [6] is shown as a green dashed 37 line). 38 39…”
Section: Introductionmentioning
confidence: 99%
“…Another irradiation induced defect known to impact thermal transport are voids . While the majority of vacancies created under displacement damage recombine with interstitials, a very small fraction of them is expected to cluster into voids .…”
Section: Resultsmentioning
confidence: 99%
“…These latter phenomena have been actively investigated by computational methods 19,45,46 and very little experimental data exist and are a subject of future work. 47,48 The stopping and range of ions in matter (SRIM) code was used to estimate the displacement damage.…”
Section: Measurements In Ion Irradiated Materialsmentioning
confidence: 99%